Multiple brain abscesses treated by extraction of the maxillary molars with chronic apical lesion to remove the source of infection - Ki-Hyun Jung; Seong-Su Ro; Seong-Won Lee; Jae-Yoon Jeon; Chang-Joo Park; Kyung-Gyun Hwang (SpringerOpen, 2019)
Abstract Background Brain abscess is a life-threatening condition that occurs due to complications during a neurosurgical procedure, direct cranial trauma, or the presence of local or distal infection. Infection in the oral cavity can also be considered a source of brain abscess. Case presentation A 45-year-old male patient was transported with brain abscess in the subcortical white matter. Navigation-guided abscess aspiration and drainage was performed in the right mid-frontal lobe, but the symptoms continued to worsen after the procedure. A panoramic radiograph showed alveolar bone resorption around the maxillary molars. The compromised maxillary molars were extracted under local anesthesia, and antibiotics were applied based on findings from bacterial culture. A brain MRI confirmed that the three brain abscesses in the frontal lobe were reduced in size, and the patient's symptoms began to improve after the extractions. Conclusion This is a rare case report about multiple uncontrolled brain abscesses treated by removal of infection through the extraction of maxillary molars with odontogenic infection. Untreated odontogenic infection can also be considered a cause of brain abscess. Therefore, it is necessary to recognize the possibility that untreated odontogenic infection can lead to serious systemic inflammatory diseases such as brain abscess. Through a multidisciplinary approach to diagnosis and treatment, physicians should be encouraged to consider odontogenic infections as a potential cause of brain abscesses.